Re-evaluating the volume effect in double-gate tunnel field effect transistors - Bui Huu Thai (Nhà xuất bản Bách Khoa Hà Nội, 2024)
Tunnel field effect transistors (TFETs) exhibit a potential candidate for ultra-low power integrated circuits because the conduction mechanism of band-to-band tunneling (BTBT) allows their subthreshold swing less than the thermal limit of 60 mV/decade at room temperature. Like conventional MOSFETs, scaling down the device size and using the multi-gate structure are important methods to enhance the TFET performance and application. Until now, the volume effect has been considered as the main cause of the on-current degradation when scaling the body thickness of double-gate TFET. In this study, the volume effect was investigated in detail to re-evaluate its impact on the on-current of TFETs. Based on two-dimensional device simulations, it was shown that the volume effect is not responsible for the decrease of on-current with thinning the body down to even several nanometers. This is because the BTBT regions that contribute greatly to the on-current are extremely small and close to the gate-oxide surfaces. The BTBT is generated mostly in the regions with the smallest width of tunnel barrier because the BTBT probability is exponentially decreased with increasing the barrier width. Exactly understanding the impact of the volume effect is necessary to properly study and design scaled TFET devices.